TARGET APPROACH TO PROJECT FINANCING TRANCHES OF INNOVATIONS AND INVESTMENTS - Galina G. Balayan (Модернизация, инновация, развитие, 2015)
The article concerns the main provisions of the financing tranches for innovative projects. The article is of methodological nature. It gives theoretically justified, universal for any of the project stages and their characteristics needed to calculate efficiency project financing tranches.